Feed-in Tariff for Renewable Energy Development in Malaysia: A Legal Study on New Energy: (Tarif Galakan bagi Pembangunan Tenaga Boleh Baharu di Malaysia: Suatu Kajian Perundangan Tenaga Baharu) (Kanun: Jurnal Undang-undang Malaysia, 2018)
The government's target for obtaining 5 percent of the country's energy from renewable energy sources (RE) in 2015 has not yet been achieved. Notwithstanding the fact that the Renewable Energy Act 2011 (Act 725) has been enacted as the primary means to increase RE generation, which provides feed-in tariff (FiT) mechanisms. This paper aims to identify existing policies and laws in Malaysia relevant to FiT, as well as the scope of the law applicable to increase electricity generation from RE in Malaysia. The findings show that FiT mechanisms have been successful in establishing RE market for electricity generation in various jurisdictions. However, FiT is unable to guarantee the sustainability of energy sources in the country. Through this article, it is found that the diversity of legal instruments is vital for long-term RE expansion.Keywords: Renewable energy, feed-in tariff, environmental sustainability, incentive, policy.